Ant1 mutant mice bridge the mitochondrial and serotonergic dysfunctions in bipolar disorder. Issue 10 (October 2018) - Kato, Tomoaki; Kubota-Sakashita, Mie; Fujimori-Tonou, Noriko; Saitow, Fumihito; Fuke, Satoshi; Masuda, Akira; Itohara, Shigeyoshi; Suzuki, Hidenori; Kato, Tadafumi
Abstract Although mitochondrial and serotonergic dysfunctions have been implicated in the etiology of bipolar disorder (BD), the relationship between these unrelated pathways has not been elucidated. A family of BD and chronic progressive external ophthalmoplegia (CPEO) caused by a mutation of the mitochondrial adenine nucleotide translocator 1 (ANT1, SLC25A4 ) implicated thatANT1 mutations confer a risk of BD. Here, we sequencedANT1 in 324 probands of NIMH bipolar disorder pedigrees and identified two BD patients carrying heterozygous loss-of-function mutations. Behavioral analysis of brain specificAnt1 heterozygous conditional knockout (cKO) mice using lntelliCage showed a selective diminution in delay discounting. Delay discounting is the choice of smaller but immediate reward than larger but delayed reward and an index of impulsivity. Diminution of delay discounting suggests an increase in serotonergic activity. This finding was replicated by a 5-choice serial reaction time test. An anatomical screen showed accumulation of COX (cytochrome c oxidase) negative cells in dorsal raphe. Dorsal raphe neurons in the heterozygous cKO showed hyperexcitability, along with enhanced serotonin turnover in the nucleus accumbens and upregulation ofMaob in dorsal raphe. These findings altogether suggest that mitochondrial dysfunction as the genetic risk of BD may cause vulnerability to BD by altering serotonergic neurotransmission.